2010 6th World Congress on Services 2010
DOI: 10.1109/services.2010.45
|View full text |Cite
|
Sign up to set email alerts
|

Service Storm: A Self-Service Telecommunication Service Delivery Platform with Platform-as-a-Service Technology

Abstract: Abstract-To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…where Q −1 (x) is the inverse of the Gaussian Q function. Formula (5) indicates that the computation result of L u bits is encoded into a code-word block of l u symbols, and subsequently transmitted by the network operator [16]. It should be pointed out that the premise of the approximation here is that l u ≥ l min , where l min is the shortest blocklength.…”
Section: Computation and Communication Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where Q −1 (x) is the inverse of the Gaussian Q function. Formula (5) indicates that the computation result of L u bits is encoded into a code-word block of l u symbols, and subsequently transmitted by the network operator [16]. It should be pointed out that the premise of the approximation here is that l u ≥ l min , where l min is the shortest blocklength.…”
Section: Computation and Communication Modelmentioning
confidence: 99%
“…In the trading market, service providers rely on their service delivery resources, such as Information Technology (IT) infrastructure (i.e. large data centres), to dominate the content distribution for profitability [4][5][6]. Network operators, in addition to providing basic communication links, can also rent out edge computing resources near access points (APs) to earn revenue [7].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al (2015) pointed out that with the development of customer capability in technology and mobile self-service, customers have personalized service experience based on their specific knowledge and skills. Zhou et al (2010) suggested using Platform-as-a-Service (PaaS), whereby services are more targeted, focused, and personalized to maintain customer loyalty and increase an organization's revenue. On the other hand, Riahi and Ristock (2014) proposed conventional interaction, whereby a contact centre provides a centralized customer service handled by live agents who, for example, answer telephone calls, respond to emails, and conduct live chats, and make outbound calls.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the major difference between onsite and online application model [5]. Cloud computing enables telecom operators to offer communication services at reduced price for subscribers and ability for serving the next generations of terminals like smartphones, tablets, and new generation wearable devices [3]. Cloud computing provides a new business opportunity for Telecom Service Providers (TSP) who are well positioned to combine cloud computing services with securely managed networking to meet the customer requirements for secure and high performance cloud services.…”
Section: Introductionmentioning
confidence: 99%
“…Cloud computing provides a new business opportunity for Telecom Service Providers (TSP) who are well positioned to combine cloud computing services with securely managed networking to meet the customer requirements for secure and high performance cloud services. Onsite and Online application model [5] Cloud computing has the potential to affect the operational and revenue models of the telecom sector [3]. The cloud computing can impact on telecom Operations Support System (OSS) and Business Support Systems (BSS) which control the primary and supporting activities of the telecom business [9].…”
Section: Introductionmentioning
confidence: 99%